Combined positioning algorithm based on BeiDou navigation satellite system and raw 5G observations. (28th February 2022) - Li, Fangxin; Tu, Rui; Hong, Ju; Zhang, Shixuan; Zhang, Pengfei; Lu, Xiaochun
Highlights: Proposed a combined positioning algorithm with BDS and 5G that is based on raw observations. It is suitable for the environment with the geometric distribution of satellites was uneven or the number of visible satellites was insufficient. Positioning algorithm of TDOA based on 5G millimeter wave. Abstract: In environments such as urban canyons and indoor environments, an insufficient number of visible satellites can degrade the positioning performance of the BeiDou Navigation Satellite System (BDS). Thus, a positioning algorithm that combines the BDS and 5G technology was developed based on raw observation data. Three different satellite occlusion environments were simulated to compare the effects of factors such as the number of base stations and geometric configurations on the positioning performance. The experimental results revealed that the introduction of 5G base stations effectively increased the positioning accuracy and reliability under different occlusion conditions. Additionally, increasing the number of base stations and optimizing the geometric configuration further improved the accuracy and reliability of fusion localization. Moreover, the positive effects of the introduction of 5G base stations were stronger under more severe satellite occlusion conditions. In the future, this fusion positioning algorithm is expected to facilitate the realization of seamless indoor and outdoor positioning.